Upaya Peningkatan Wisata di Jakarta melalui Museum: StrategiPengembangan Museum Nasional Indonesia - Daranca, Unira (Journal of Indonesian Tourism and Policy Studies, 2016)
Museum as a center of cultural information could be an interesting place to visit. In fact, the museum is often looked as frightening space or even dull for society. The layouting of museum itself and less attraction perceived to be one of the reasons why people seldom visited museums. To make the museum into a pleasant place and visited by many tourists, it would require some strategies. The strategy itself certainly can be used as a tourist attraction to come to visit the museum. Various strategies undertaken by the museum, often manifested by convening various interesting activities program. These programs could be displayed as an art attraction, exhibitions, or held competitions with prizes. The National Museum is the main object in this paper. Under the slogan Goes to Museum, National Museum implemented the strategy by issuing various activity programs. The result of this study is to see how the implementation of the slogan Goes to Museum inherited into program activities. National Museum Indonesia is considered successful in increasing tourist visits museums in Jakarta. This was reflected in the number of program activities at the National Museum of Indonesia, which brings a lot of tourists, both domestic and foreign tourists. The main reason of the programs which carried by the National Museum of Indonesia, is how to package the educational content of history and culture in a fun way and not boring at all. National Museum of Indonesia aware that, through an interesting way, the information that have been provided will be more quickly understood by tourists, especially for students who come from various levels of education. National Museum of Indonesia through the slogan Goes to the museum, consistently brings programs interesting activities to increase tourists, especially tourists who traveled in Jakarta